Help or harm : the human security effects of international NGOs - Murdie, Amanda, 1980- (Stanford University Press, 2014)
Do international non-governmental organizations (INGOs) matter? When do they influence human security? This book offers a comprehensive framework for understanding the effects of international non-governmental organizations (international NGOs or INGOs) on a variety of human rights and development outcomes.